answersLogoWhite

0


Top Answer
User Avatar
Name
Answered 2021-04-15 01:12:20

so you are talking about 2x^2 - 11x + 14 ... So then you found the Common factor from the two pairs. Then you would do 2x^2 - 4x - 7x + 14. 2(x^2-2x) - (7x-2). If you rewrite it in factor form, then it would be (2x−7)(x−2). If you try to find what x is, then you would have two different sets now. 2x - 7 and x - 2. Move the number to the other side... 2x = 7 and x = 2. (2x = 7) = (x = 7/2).

Simply the equation: (2x−7)(x−2)

Solving for x: x = 7/2 or 2

012
🙏
0
🤨
0
😮
0
😂
0
User Avatar

Your Answer

Loading...

Still have questions?

Related Questions

9x squared plus 11x-14 factored is?

(9x + 7)(x - 2)


What is 8 plus 11x and gt-14?

If you mean 8+11x = -14 then the value of x works out as -2


How do you factor 2x squared plus 3x minus 14?

(x - 2)(2x + 7)


How do you factor y squared minus 9y plus 14?

(y - 2)(y - 7)


What is x squared minus 9x plus 14?

It is: (x-2)(x-7) when factored


How do you factor 2x squared minus 16x plus 14?

2(x - 7)(x - 1)


If they distance traveled is 5x3-6x2 plus 3x plus 14 mi and the rate is x plus 1 mph What is an expression for the time traveled?

Distance travelled = 5x3 - 6x2 + 3x + 14 = 5x3 + 5x2 - 11x2 - 11x + 14x + 14 = 5x2(x + 1) - 11x(x + 1) + 14(x + 1) = (x + 1)(5x2 - 11x + 14) Then time = distance/rate = (x + 1)(5x2 - 11x + 14) / (x+1) = 5x2 - 11x + 14


How do you factor 9x2 plus 11x-14?

9x2+11x-14 = (9x-7)(x+2) when factored with the help of the quadratic equation formula.


Simplify 14 plus 2x plus 9x - 6 - 11x?

14 + 2x + 9x - 6 - 11x 14 - 6 + 2x + 9x - 11x The x values cancel themselves out, leaving just the number value The answer is therefore 8.


What are the factors of the expression g squared minus 14 g plus 45?

It is: (g-5)(g-9)


How do you factor the expression x squared minus x times 14 plus 33?

You look for two integers which multiply to 33 and whose sum is 14 and these happen to be 11 and 3. So x^2 - 14x + 33 = x^2 - 3x - 11x + 33 =(x^2 - 3x) - (11x - 33) [sign for 33 changes because the bracket has a minus sign] =x * (x-3) + 11 * (x-3) =(x - 3) * (x - 11)


How do you solve minus 2x squared plus 10x minus 14 equal 0?

It can't be solved because the discriminant of this quadratic equation is less than zero


What is 24 plus 14 minus 8?

24 plus 14 minus 8 = 18


What is the answer for -2x plus 14 - 9x plus -1?

-11x + 13


X squared minus 196?

That factors to (x - 14)(x + 14)


What is x squared minus 5x minus 14?

x2-5x-14 = (x+2)(x-7) when factored


How do you factorise 12x squared minus 9x minus 14?

With the help of the quadratic equation formula


Factor the expression x squared minus 196?

(x - 14)(x + 14)


Factoring 2x2-11x plus 14?

(2x - 7)(x - 2)


What is 18x squared minus 9x minus 14 equals 0?

x = -2/3,7/6


What is 14 squared plus 14 squared equals what squared?

14 squared = 196, so you're looking for the sqrt of double that, ie 392, which is almost exactly 19.8


Is 4h squared minus 56 factorable?

4(h2 - 14)


What is 3 plus 6 minus 2 plus 14 minus 3 plus 2?

3 + 6 - 2 + 14 - 3 + 2 = 20


What is 4 minus 7 plus 14 plus 2 minus 19 plus 6?

4 - 7 + 14 + 2 - 19 + 6 = 0


How do you factor 2x2 11x 14'?

If that's +11x + 14, the answer is (x + 2)(2x + 7)